2019
DOI: 10.1088/2058-6272/aaf368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-vacuum helium cold plasma pre-treatment on the rooting and root growth of zoysiagrass (Zoysia Willd.) stolon cuttings

Abstract: The influence of low-vacuum helium cold plasma treatment on the rooting percentage, root growth and physiochemical properties of zoysiagrass stolon cuttings was studied. Zoysiagrass stolon cuttings were pre-treated with 0, 100, 200, 300 and 400 W of cold plasma for 15 s. The cold plasma positively stimulated rooting and improved the root growth of the zoysiagrass stolon cuttings, and the 300 W treatment produced the best effect. The rooting percentage and root growth parameters, including the root length, tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In this study, both positive and inhibitory responses associated with the plasma priming in C. roseus are presented. In line with our findings, numerous reports are exhibiting the growth‐stimulating function of plasma priming in diverse plant species, while little evidence exists on growth‐inhibitory or delaying response following plasma application . Taking the plasma diagnostic data into account, we recently reported that the optical emission spectroscopy‐based spectrum confirmed the generation of oxygen‐ and nitrogen‐related species, as well as UV photons during the plasma generation .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, both positive and inhibitory responses associated with the plasma priming in C. roseus are presented. In line with our findings, numerous reports are exhibiting the growth‐stimulating function of plasma priming in diverse plant species, while little evidence exists on growth‐inhibitory or delaying response following plasma application . Taking the plasma diagnostic data into account, we recently reported that the optical emission spectroscopy‐based spectrum confirmed the generation of oxygen‐ and nitrogen‐related species, as well as UV photons during the plasma generation .…”
Section: Discussionsupporting
confidence: 90%
“…As mentioned earlier, enhanced seedling growth without changes to the germination efficiency has been also observed after plasma treatment [15,19,41,44,56,59,64]. Plasma treatment at the seedling stage has also reported, which promoted seedling growth [10,48,55,61,63]. As for seed germination, the effects of plasma on seedling growth varies with the plasma dose, treatment time, feeding gases, and moisture.…”
Section: Effects Of Plasma On Plant Vegetative Growth and Reproductionmentioning
confidence: 67%
“…The positive effect of plasma on seed processes related to catalase action has been proven [174]. Many researchers have confirmed the positive effect of plasma on plant rooting process, especially the increase in the length and number of formed roots [175,176]. Plant hormones-auxins-are the most important chemical substances in the process of rhizogenesis [177].…”
Section: Plasmamentioning
confidence: 98%